Relevancy and admissibility of child testimony: a comparative appraisal - Mohamad Yunus, Mohamad Ismail (Serial Publications, 2017)
Recently, there has been substantial increase in the number of criminal cases involving sexual crimes against children. Fortunately, due to society’s encouragement and concern on the problem, children are starting to speak out and parents, teachers, social service agencies, law enforcement as well as prosecution started to listen to them and the Parliament also has recently passed the legislation on Sexual Offences Against Children 2017. The question is what makes the sexual abuse of children different from other criminal cases is because of the victim are children. Referring to the definition of child under Child Act 2001, it is defined as a person under the age of eighteen years. It is the nature of children that they are particularly vulnerable as victims of the crime. In addition, the fact that mostly children are physically fragile and smaller, naive and young made them are less able to articulate their experiences and feeling if being victimized